The farm of the past and the future - Reed, Robert Stirling (My University, 1892)
Introduction: The farmer has been spoken of today, but I wish to speak especially of the farm. In nature, all living beings must have nourishment to preserve life. Plants abstract their living from the soil; lower animals feed on plants and other animals; man, the culmination of earthly life, must also look to lower beings and to mother earth for his sustenance; and since the days of Adam, that sustenance has been given only as the reward of toil. At first, I presence this toil was of the simplest and rudest nature and consisted in gathering his food from whatever he could find. But he is a progressive being, full of inquisitiveness, and he soon saw that a little attention to growing nature would assist its productiveness greatly. This was the foundation of farming.
Citation: Reed, Robert Stirling. The farm of the past and the future. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Farm; Development; Agriculture; Theses; Manuscripts (documents)